Theoretical ground for adsorptive therapy of anthracyclines cardiotoxicity - Shevchuk, O.O.; Posokhova, E.A.; Sakhno, L.A.; Nikolaev, V.G. (Experimental Oncology, 2012)
Anthracyclines play an important role in treatment of variety types of cancer due to their high effectiveness and broad spectrum of activity. However, a major limitation of their use is the dose-limiting cardiotoxicity. The inability to predict and prevent anthracycline cardiotoxicity is in part due to the fact that the molecular and cellular mechanisms remain controversial and incompletely understood. This review focuses on the biochemical basis of the anthracyclines toxic cardiac effects and pharmacological measures to their treatment and preventing. We describe the theoretical substantiation of the enterosorption abilities for diminishing of cardiac damage.